Rancang Bangun Sistem Insentif untuk Meningkatkan Pendapatan Petani, Efisiensi Penggunaan Air dan Ketahanan Pangan - Bambang Juanda (Jurnal Ilmu Pertanian Indonesia, 2012)
Increasing productivity of rice generally depends on a variety of additional inputs. Various systems are designed for farmers to increase incomes and improve land productivity. SRI method is a potential technology to increase rice production management based on the cultivation of land, plants and water through the empowerment of groups and local knowledge-based eco-friendly activities. The application of SRI method requires a study of innovation adoption and optimal strategies for farmers. This study uses institutional descriptive analysis; LFA (Logical Framework Analysis) and experimental economics. The results showed that (1) The role and focus of government institutions is an increase in production through the application of various technologies. Performance of local institutions have an important a role of cultivation introduction and depends on the active community leader or head of the farmer or P3A Mitra Cai; (2) Incentives system for farmers in the application SRI paddy method is marketing insurance with favorable price, (3) the application of SRI paddy cultivation requires strengthening group farmer and P3A Mitra Cai in regulating water, organic agricultural input and marketing of products through the application of water fee rates (ipair) based on fair remuneration system; and (4) the incentives for farmers to encourage the application of SRI paddy cultivation is the provision compensation if there is a decrease in production. The existence of information on SRI Method have real impact.